An Astronomical Diary: or Almanack, For the Year of Christian Aera 1795. Being the third year after Bissextile, or Leap-Year; and the Nineteenth of the Independence of America, which began July 4th, 1776. - Low, Nathanael, 1792-1883. (Tufts University. Tisch Library., 2018)
12 leaves [Tisch Library copy contains 10, 8 of which appear to be original to this volume, and contains handwritten annotations].